PENGARUH KUALITAS PRODUK DAN SUASANA TOKO TERHADAP KEPUASAN KONSUMEN DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO AKSESORIS BINTANG SEMBILAN DI SITUBONDO - Arifandi, Arifandi; Ediyanto, Ediyanto; Praja, Yudha (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
Marketing is one of the main activities that needs to be carried out by a company, be it a goods or service company, in an effort to maintain the viability of its business. The purpose of this study was to analyze and test the effect of product quality and store atmosphere on consumer confidence with consumer satisfaction as an intervening variable at the Bintang Sembilan accessories store in Situbondo. The population in this study are consumers of the Bintang Sembilan Accessories Store in Situbondo Regency. The sampling method is determined by probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM).The results of the direct effect hypothesis test using the Smart PLS 3.0 application, show that product quality has a significant positive effect on consumer confidence. Store atmosphere has a significant positive effect on consumer confidence. Product quality has a positive but not significant effect on consumer satisfaction. Store atmosphere has a significant positive effect on consumer satisfaction. Consumer trust has a significant positive effect on consumer satisfaction. Product quality on consumer satisfaction through consumer trust has a significant positive effect. Store atmosphere on consumer satisfaction through consumer trust has a significant positive effect.